Qualitative Methods in Special Education Research. Issue 4 (4th November 2021) - Leko, Melinda M.; Cook, Bryan G.; Cook, Lysandra
Abstract: Qualitative research methods are used within special education research to provide insights about how and why phenomena occur. They can, however, be misunderstood and applied inappropriately. Our aim in this article is to provide an overview of qualitative methods, including their purpose, contributions to research involving students with learning disabilities, limitations, and quality indicators for methodological rigor. Additionally, we highlight common qualitative methods and data sources. We review a recent study that exemplifies the use of qualitative methods in the field. Our take‐home message is that qualitative methods can provide valuable in‐depth information about how and why phenomena occur, but they are not intended to support causal relationships or large‐scale generalizability.